Interconnection of Nanoparticles within 2D Superlattices of PbS/Oleic Acid Thin Films. (11th March 2014) - Simon, Paul; Bahrig, Lydia; Baburin, Igor A.; Formanek, Petr; Röder, Falk; Sickmann, Jan; Hickey, Stephen G.; Eychmüller, Alexander; Lichte, Hannes; Kniep, Rüdiger; Rosseeva, Elena
<x xml:space="preserve">Abstract</x> Make it connected! 2D close‐packed layers of inorganic nanoparticles are interconnected by organic fibrils of oleic acid as clearly visualized by electron holography. These fibrils can be mineralised by PbS to transform an organic‐inorganic framework to a completely interconnected inorganic semiconducting 2D array. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>